Image Guided Sclerotherapy of Masseteric Venous Malformations. (June 2020) - Kumar, Subhash; Bhavana, Kranti; Kumar, Bindey; Sinha, Amit Kumar; Kumar, Prem
Objective: To describe results of image guided sclerotherapy of venous malformations (VM) localized in the masseter muscle. Methods: Retrospective review of prospectively maintained data was done to include consecutive cases treated over 5-year period, with minimum 6 months follow-up. Sclerotherapy was done using ultrasound (US) guided needle puncture(s) of the lesions percutaneously, and 3% polidocanol foam injected under image guidance. Results: Seventeen cases (10 male, 7 female) with mean age 15.6 years (range 6-28 years) were identified. Clinical presentation was with facial asymmetry, becoming pronounced on jaw clenching, and three cases had mild local pain. On US, the lesions appeared as partially compressible masses with anechoic spaces, showing color filling on releasing probe pressure. Fourteen had phleboliths. Eight patients had undergone magnetic resonance imaging, lesions appearing as oval, homogenous, lobulated, T2 hyperintense masses, with heterogeneous contrast enhancement. Number of sclerotherapy sessions were—single in four cases, two in eight cases and three in five cases, for total of 35 sessions (average 2.05 session per patient). The mean dose of drug injected per session was 1.85 mL and total mean dose per patient was 2.79 mL. Post-procedure vomiting occurred in one patient while all had local swelling and mild pain, lasting between 3 to 7 days. No facial nerve palsy or sloughing/ulceration/skin necrosis was noted. On US follow-up (6-26 months, mean 15.9 months), 12 patients had small echogenic masses without any vascularity, and five had small anechoic areas <25%. All patients had complete resolution of swelling and pain. Conclusions: For VMs localized to the masseter muscle, image guided sclerotherapy is highly effective and safe, and recommended as first line treatment.